Percutaneous nephrolithotomy with or without nephrostomy tube (Bangabandhu Sheikh Mujib Medical University Journal, 2018)
The study has been designed to compare the outcome of percutaneous nephrolithotomy with (Group A) or without nephrostomy tube (Group B) for the management of renal stone disease. JJ stents were given to all cases of both groups. Comparison of outcome between groups shows that urinary leakage time was significantly longer in Group B than that in Group A (24.0 ± 6.2 vs 7.3 ± 3.9 hours;  p